Puitisasi Terjemahan Quran: Studi Analisis Terjemahan Quran Bersajak Bahasa Aceh - Bilmauidhah Bilmauidhah (JURNAL INDO-ISLAMIKA, 2011)
This article discusses the poetic style of the Qur’anic translation. It demonstrates that the poetic style of the Qur’anic translation has become an instrument in revealing the beauty of the Qur’an. Showing that poem or poetry is one aspect of literature which posses a lofty esthetical value, it argues that Mahjiddin’s technique of translation is truly concerned with writing style, lexical choice, structure, tone and voice as found in poem or poetry, and that the poetic style or form of translation will not change the accuration of meaning and comprehension of texts in the Qur’an.